Ethical foundations and principles for collaborative research with Inuit and their governments - Felt, Lawrence; Natcher, David (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2011)
Academic research in Canada involving Aboriginal peoples has changed dramatically during the last 20 years. From an academic researcher’s perspective, the changes have recently become formalised in the release of the 2nd edition of the Tri-Council Policy Statement on Ethics in Human Research. In this article we examine similarities and differences in the way ethical review is constructed and approached from university, Aboriginal and, in particular, Inuit perspectives. We begin our argument with a general comparison of research ethics as expressed in academic and Aboriginal sources in order to find areas of commonality, difference, and potential ambiguity between the two perspectives. We then briefly review our own experience with a multiyear research project involving several Inuit governments of different spatial and administrative scales. We conclude with discussion of a common issue arising from academic research, including our own work with Inuit and the research ethics board chaired by one of the authors. It concerns how to address potential tension between critical inquiry associated with Western scientific paradigms and respect and use of Inuit knowledge within a collaborative research process. In conclusion, we offer some “best practice advice” to academic researchers who face such a dilemma.